School Climate and the Elementary-School Counselor: A Comparative Study - Wittmer, Joe; Myrick, Robert D. (Canadian Journal of Counselling and Psychotherapy, 1972)
It was the purpose of this study to compare the interpersonal climates of elementary schools with and without counselors. Ten public elementary schools from two Florida counties were selected to participate in the investigation. All teachers from the 10 schools, 93 from the 5 schools without counselors and 118 from the 5 schools with counselors, were administered the Survey of Interpersonal Relationships. Results tend to support the concept that an elementary-school counselor makes a difference in a school's climate.